Parental surveillance of OCD and mental health symptoms during COVID-19: A longitudinal study of Australian children, adolescents and families. (August 2022) - Kroon, Rianca; Bothma, Nicole; Mathieu, Sharna; Fontenelle, Leonardo F.; Farrell, Lara J.
Abstract: To ensure the needs of children and families are met for the remainder of the COVID-19 situation and beyond there is a demand for a specific response strategy. This longitudinal study will investigate the impact of COVID-19 on Australian parental and childhood mental health symptoms, particularly OCD symptoms, examining the stability of this relationship over time and the needs and preferences for mental health support in response to child symptoms. A total of 141 parents completed a questionnaire during the lockdown period in Australia (June–September 2020). Thirty-five of them completed a follow-up questionnaire during the post-lockdown period (November 2020–January 2021). The questionnaire assessed COVID-19 experiences/worries/knowledge, child OCD, and child/parental anxiety and depression. Sub-samples of youth were determined based on parent-report of an existing diagnosis of any mental health (n = 24), of OCD (n = 22), or no mental health diagnosis (i.e., healthy, n = 81). Results: Parents reported a significant positive association between increased parental worries regarding COVID-19, and their own as well as their child's mental health symptoms. The current sample of children experienced elevated symptom severity for OCD symptoms during COVID-19. The OCD group reported significant reductions in child OCD symptoms at post-lockdown. The any mental health diagnosed children are at greater risk of developing OCD symptoms and reported strong preferences for increased support as a result. The exploratory nature of this study adds further insight into the impact of the COVID-19 pandemic on child OCD and parent mental health symptoms and the stability of symptoms over time.